The power of the diocesan bishop with regard to the administration of ecclesiastical goods of public juridic persons subject to him: An analysis of canon 1276, section 2 - Omorogbe, Edwin N (University of Ottawa (Canada), 2011)
The current norms on the administration of temporalities demand a new openness and a mutual trust between those who administer Church property and those who donate temporal goods to the Church. The entire matter of regulating how donated goods are managed is the subject matter of canon 1276. Canon 392, §2 stipulates that the diocesan bishop has an obligation to ensure that abuses do not creep into the administration of ecclesiastical goods. The legislator recognizes the fact that if abuses creep into the administration of ecclesiastical goods this will damage the credibility of the Church. The transparency and accountability of administrators are vital to sustaining this credibility. How is the diocesan bishop to ensure this transparency and accountability? The specific way of achieving this is the subject matter of our dissertation. In order to achieve this goal the dissertation was divided into four chapters. The first chapter examined the power of the diocesan bishop with regard to caring for ecclesiastical goods. The second chapter studied the roles of those who administer ecclesiastical goods. The third chapter examined the very nature of the special instructions that the diocesan bishop is expected to issue for administrators, while the fourth chapter considered the contents of this special instructions. Ecclesiastical goods assist the Church in fulfilling its mission. There is a correlation between ecclesiastical goods and the mission of the Church. Therefore, the mission of the Church is the same as the reasons why a public juridic person own goods. The same concern and due diligence that is shown to ensure that abuses do not creep into the proper celebration of the sacraments is to be shown to ensure the proper administration of ecclesiastical goods (c. 392, §2); We strongly hold that the obligation to issue special instructions for administrators of ecclesiastical goods is one of the major functions of a diocesan bishop, a function that he must consider as part of the mission which has been entrusted to him to fulfill. The special instructions serve as a canonical proactive measure to forestall possible financial malfeasance within the Church. If the Church is to avoid expending its energy and ecclesiastical resources in solving financial crisis in the future, the diocesan instruction for administrators of ecclesiastical goods should be a must for all dioceses.
Keywords: Canon Law.; Law.